2020
DOI: 10.1159/000505933
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Immune Checkpoint Inhibitors with or without a Combination of Tyrosine Kinase Inhibitors on Organ-Specific Efficacy and Macrovascular Invasion in Advanced Hepatocellular Carcinoma

Abstract: Introduction: The tumor microenvironments of different organs often differ and thus may affect the immunotherapy response. Objective: This study elucidated that the efficacy of programmed cell death protein-1 (PD-1) inhibitors varies across different metastatic sites among individuals with advanced hepatocellular carcinoma (HCC). Methods: We retrospectively analyzed treatment outcomes in advanced HCC patients receiving PD-1 inhibitors with or without a combination of tyrosine kinase inhibitors (TKIs). Both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 26 publications
7
40
0
Order By: Relevance
“…Our findings are in agreement with a report which addressed a complete response of IVCT to ICIs in advanced-stage renal cell carcinoma and proposed the response of vascular thrombi to ICIs being stronger in a high T-cell inflamed tumor microenvironment [22]. These findings indicate that ICIs markedly decrease or stabilize tumor thrombus volume, and this response may be affected by the diversity of tumor microenvironments [13,14,23]. In addition, the regression of vascular metastases may preserve organ function and prevent distant metastasis, thus offering further curative treatment either alone or in combination with other modalities for non-responding organs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in agreement with a report which addressed a complete response of IVCT to ICIs in advanced-stage renal cell carcinoma and proposed the response of vascular thrombi to ICIs being stronger in a high T-cell inflamed tumor microenvironment [22]. These findings indicate that ICIs markedly decrease or stabilize tumor thrombus volume, and this response may be affected by the diversity of tumor microenvironments [13,14,23]. In addition, the regression of vascular metastases may preserve organ function and prevent distant metastasis, thus offering further curative treatment either alone or in combination with other modalities for non-responding organs.…”
Section: Discussionsupporting
confidence: 93%
“…To assess the vascular response, the largest diameters of the tumor thrombus were measured and compared with the basal value recorded [ 21 ] and categorized as follows: complete remission (CR), i.e., complete disappearance of the tumor thrombus; partial response (PR), i.e., at least a 30% decrease in thrombus diameters; stable disease (SD), i.e., a decrease of < 30% or an increase of < 20%; and progressive disease (PD), i.e., an increase of ≥ 20% in the sum of the diameters [ 13 ]. Objective response rate of tumor thrombi (ORRT) was defined as the total number of patients achieving CR or PR, and disease control rate of tumor thrombi (DCRT) was defined as the total number of patients achieving CR, PR, or SD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of the latter explanation, recent clinical trials in advanced HCC have shown a trend for higher ORRs overall with combined TKI and anti-PD-1 antibody therapy (13,25) versus anti-PD-1 antibody monotherapy (26) or dual immune-therapy strategies. (27,28) Finally, in the present study, the OSRR for lung metastases was similar to previous reports of immune checkpoint inhibitor monotherapy (37 vs. 40% (16) and 41.2% (17)). However, due to the small number of patients with lung metastasis included in the present study, the conclusions that can be drawn are limited.…”
Section: Discussionsupporting
confidence: 91%
“…There have been previous reports of organ-speci c responses to immunotherapy in the second-line treatment of HCC. (16,17) However, to our knowledge, this is the rst report of organ-speci c responses to rst-line combination treatment with lenvatinib plus anti-PD-1 antibodies in patients with advanced HCC.…”
Section: Discussionmentioning
confidence: 91%